Profit at the expense of health. Irresponsible corporate communication in the supplements industry - García-Arranz, Ana (2024)
The growing concern over health and nutrition have led to the proliferation in the consumption of supplements worldwide. In Europe, the market size has reached 13,300 million euros in 2022. Nevertheless, consumers remain uninformed and deceived by products that presume to be remedies for even the most serious diseases. In the context of an industry, in which legal gaps have allowed profitability to displace ethics, it seems urgent to analyze the degree of (ir)responsibility of companies in managing the transparency of the information they provide to the consumer. This work aims to evaluate the transparency of supplements enterprises’ corporate communication, exploring three different dimensions of the information provided: disclosure, clarity, and accuracy. A quantitative approach and descriptive statistics were performed using χ2, based on the content analysis of 103 corporate websites. This corpus encompasses the entire universe of companies that invested in digital advertising between the years 2017 and 2021. Results show that 61.2% of enterprises do not declare themselves socially responsible on their websites, and only 13 out of 113 have issued transparency reports; product information is confusing in 45.6% of companies and lacking in 19.4%; ingredients are absent in more than half of the corpus, and empirical evidence is omitted in 83.5% of enterprises.